2016
DOI: 10.1016/j.ygyno.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 10-year survivors of high-grade serous ovarian carcinoma

Abstract: Objective High-grade serous carcinoma (HGSC) generally presents at an advanced stage with poor long-term (LT) survival. Here we describe clinical features found in women surviving HGSC for ten or more years. Methods A multi-center research consortium was established between five participating academic centers. Patient selection criteria included high-grade serous ovarian, fallopian tube, or peritoneal carcinoma with at least ten years of follow up. Non-serous, borderline tumors and low-grade serous subtypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 15 publications
2
52
0
Order By: Relevance
“…Unfortunately the model’s predictive ability (AUC of 0.729) was insufficient for clinical utility as defined by the ability to discriminate long-term survivors sufficiently to alter patient management in ways that might ultimately improve outcomes [24]. Researchers from a multi-center research consortium investigating 10-year long-term survival highlighted the lack of predictability of clinical factors finding that 14% of long-term survival patients had suboptimal cytoreduction, 11% had an initial platinum free interval less than 12 months, and 53% had recurrent disease [19]. Though not evaluated in this analysis, successful prediction of long-term survivorship will likely depend on factors beyond currently recognized clinicopathologic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately the model’s predictive ability (AUC of 0.729) was insufficient for clinical utility as defined by the ability to discriminate long-term survivors sufficiently to alter patient management in ways that might ultimately improve outcomes [24]. Researchers from a multi-center research consortium investigating 10-year long-term survival highlighted the lack of predictability of clinical factors finding that 14% of long-term survival patients had suboptimal cytoreduction, 11% had an initial platinum free interval less than 12 months, and 53% had recurrent disease [19]. Though not evaluated in this analysis, successful prediction of long-term survivorship will likely depend on factors beyond currently recognized clinicopathologic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, as well as other retrospective studies of patients in the United States have found a survival benefit for primary debulking surgery among patients with stage IIIC disease (10, 11). These studies are subject to selection bias and confounding by indication, however, at this time, primary cytoreductive surgery for patients who are selected to undergo it, seems to be associated with the longest survival (21, 22). It is, therefore, possible that for patients with resectable disease, upfront cytoreductive surgery is associated with both increased short-term complications and increased long-term survival (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Women with stage III disease have 5- and 10-year survival rates of 36% and 23%, respectively, with rates of 17% and 8% for stage IV disease [1]. Clinical predictors of long-term survival have recently been described [2]; however, quality of life (QOL) and survivorship concerns of long-term advanced-stage survivors have been minimally characterized, thus little is known about the needs of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Although ovarian cancer patients have been surviving longer [9, 10] there has been minimal characterization of QOL needs of advanced-stage ovarian cancer patients surviving for 8.5 years or longer post-diagnosis. Furthermore, there is substantial heterogeneity in disease course among long-term survivors [2]. Although some live for many years recurrence-free and disease-free, others have multiple recurrences, and may have long-lasting intermittent treatment.…”
Section: Introductionmentioning
confidence: 99%